Challenges and risks of using Omega-3 fatty acids in the supportive treatment of depression - Orzechowska, Joanna; Orzechowski, Michał; Fijałek, Paulina; Karczmarz, Jan; Paprocka, Aleksandra; Gutowska, Marika; Kosińska, Agnieszka; Świrk, Urszula; Belcarz, Wiktoria; Kalinowska, Karolina (Quality in Sport, 2025)
Introduction: Omega-3 fatty acids, including α-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), are essential nutrients with anti-inflammatory and neuroprotective properties. EPA has demonstrated potential in mitigating depression by enhancing neurotransmitter synthesis, including dopamine and serotonin. However, gastrointestinal side effects, fatigue, anxiety, contamination risks (e.g., mercury, lead), and variability in supplement quality and accessibility pose significant challenges. Addressing these issues is essential to optimize the safe and effective therapeutic use of omega-3 fatty acids in depression management. Material and methods of research: The materials and literature was collected using searches in Pubmed, research gate and Google Scholar databases and references from retrieved articles. Results: Omega-3 fatty acids, particularly EPA and DHA, show promise in treating depression due to their anti-inflammatory and neuroprotective effects. However, challenges include differing mechanisms, side effects, contamination risks, and inconsistent supplement quality. Short trials often miss long-term effects, and limited access and population diversity further hinder progress. Rigorous research and improved regulation are essential to unlock their full therapeutic potential. Conclusion: Omega-3 fatty acids, particularly EPA, show promise as a supportive treatment for depression due to their role in neurotransmitter production and inflammation control. However, challenges such as side effects, contamination risks, and inconsistent supplement quality necessitate strict monitoring, improved standards, and broader access to high-quality products to ensure their safe and effective use in depression management.